(untitled) - Stephen L. Herman; Stephen L. Herman (Albany, 1999)
Electrician's Technical Reference -- Industrial Electronics covers components most used in heavy industry, such as silicon control rectifiers, triacs and more, and includes examples of common rectifiers and phase-shifting circuits. This is the perfect guidebook for anybody in the field of plant maintenance and troubleshooting. This series of technical reference books is designed to provide the electrician, electrical contractor, industrial maintenance technician, and other electrical workers with a source of reference information about virtually all of the electrical topics that they encounter. Each topic is written by an expert in that subject matter. The modular format makes this a practical reference, and the volumes are kept to a very concise and easy-to-reference size. This series is sure to answer all of the electrical questions one might encounter on the job
Keywords: Industrial electronics --Handbooks; manuals; etc